Histological study of the effects of three anti-inflammatory preparations on the gastric mucosa. Issue 8 (August 1981) - McIntyre, R L; Irani, M S; Piris, J
Abstract : Patients with osteoarthritis were entered into a single-blind trial comparing the effects on the gastric mucosa of a four week course of indomethacin, sulindac and a compound of paracetamol and dextropropoxyphene (Distalgesic). The presence and severity of both acute and chronic gastritis were assessed by histological examination of endoscopic biopsy specimens taken from five standard sites in th stomach of each patient before and at the end of the four week period. The presence and severity of chronic gastritis was not affected by the treatment in any of the groups. The pattern of acute gastritis was complex, many of the patients having acute inflammatory changes in their initial biopsy specimens. At least one patient in each treatment group developed marked acute gastritis during the treatment period, but a significant overall increase in the severity of these changes was only found in the group treated with sulindac.